Combined endoscopic transnasal and transoral approach for extensive upper cervical osteoradionecrosis - Tan, S.H.; Ganesan, D.; Rusydi, W.Z.A.; Chandran, H.; Prepageran, N.; Waran, V. (2015)
Osteoradionecrosis (ORN) is a rare yet well-recognized complication following radiotherapy to the head and neck. We illustrate the only case of a spontaneous extrusion of the sequestered C1 arch through the oral cavity and discuss our experience with a combined endoscopic transnasal and transoral approach for cervical ORN. A 56-year-old female presented with a 3-month history of blood-stained nasal discharge. She had been treated with radiotherapy for nasopharyngeal carcinoma 25 years earlier. Flexible nasal endoscopy demonstrated an exposed bone with an edematous posterior nasopharyngeal mass. Computed tomography showed a pre-vertebral mass with destruction of C1 and C2. She underwent occipito-cervical fusion followed by a combined transnasal and transoral endoscopic debridement of non-viable bone in the same perioperative setting. Healing of the raw mucosa was by secondary intention and reconstruction was not performed. Histopathological examination reported ulcerated inflamed granulation tissue with no evidence of malignancy. During follow-up, she remained neurologically intact with no recurrence. Using both nasal and oral spaces allows placement of the endoscope in the nasal cavity and surgical instruments in the oral cavity without splitting the palate. Hence, the endoscopic transnasal and transoral approach has vast potential to be effective in carefully selected cases of cervical ORN.